Sustainable fire safety solutions: bioactive natural polysaccharides and secondary metabolites as innovative fire retardants for textiles - Manoj Kumar; Mrunal D. Barbhai (Emergency Management Science and Technology, 2023)
Fire safety is a critical concern in various industries, including residential, transportation, and industrial sectors. The development of sustainable solutions for fire safety has gained significant attention in recent years. This review article explores the utilization of polysaccharide and secondary metabolites as fire retardants in textile materials, presenting a promising avenue for sustainable fire safety solutions. By harnessing the inherent fire-resistant properties of these bioactive polysaccharide and secondary metabolites, researchers aim to develop textiles with enhanced flame retardancy without compromising on sustainability. This review offers a comprehensive overview of recent advancements in this field, encompasing the selection of polysaccharides and secondary metabolites, their integration into textile materials, and the assessment of fire-retardant properties. The use of sustainable materials and compounds in the textile sector is exemplified through a comparison with traditional flame retardants. The mechanisms by which flame retardants operate, as well as case studies that focus on polysaccharides and bioactive secondary metabolites along with environmental impact and sustainability, are also emphasized in this review. The synthesis of knowledge presented in this review article contributes to the growing body of research on sustainable fire safety and provides insights for future developments in the field of fire-retardant textile materials using bioactive plant compounds.